2011
DOI: 10.1021/la203056f
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Based Dispersant for Multiwall Carbon Nanotubes to Prepare Ceramic Composites by a Sol–Gel Method

Abstract: A dispersant for multiwall carbon nanotubes (MWCNTs) is proposed that fulfils the requirements of creating a uniform dispersion in the matrix and obtaining a good interface between CNTs and the matrix, and is soluble in generic nonpolar solvents. This dispersant is based on a long chain surfactant, called in this work dabcosil stearate, containing a stearate-based 18-carbon alkyl chain as an anion, and a silsesquioxane containing a bridged, positively charged 1,4-diazoniabicyclo[2.2.2]octane group. It provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…The authors concluded their findings solely on the basis of their microstructural observations [25]. Recently, Silva et al [39] prepared alumina -CNT and zirconia -CNT nanocomposites by using surfactant based dispersants and reported good interface between the matrices and CNTs.…”
Section: Introductionmentioning
confidence: 93%
“…The authors concluded their findings solely on the basis of their microstructural observations [25]. Recently, Silva et al [39] prepared alumina -CNT and zirconia -CNT nanocomposites by using surfactant based dispersants and reported good interface between the matrices and CNTs.…”
Section: Introductionmentioning
confidence: 93%
“…Another potential application of gemini surfactants due to their ability to form micelles is the capacity to disperse insoluble in water particles and form stable colloids. Carbon nanotubes (CNT) have unique electrical, optical and mechanical properties, and due to that, they are used as medical sensors, electronics and compatible materials [260]. However, because of strong Van der Waals interactions, the bundles are insoluble in water and common organic solvents Table 3.…”
Section: Dispersionmentioning
confidence: 99%
“…To date, a variety of strategies have been employed to assemble alumina nanoparticles with CNT, including sol-gel processes [9], pressureless sintering process [10], chemical precipitation [11], and heteroaggregation process [12]. CNT-alumina nanocomposites have been synthesized by direct growth of CNT on alumina by chemical vapor deposition, then, the as-grown nanocomposites were densified by spark plasma sintering [13].…”
Section: Introductionmentioning
confidence: 99%